UJI CEPAT (RAPID TEST) ANTIBODI IgM TERHADAP Salmonella typhi DEMAM TIFOID - Rini Riyant; Prihatini .; Siti Rochmatoen (Indonesian Association of Clinical Pathologist and Medical laboratory, 2008)
Typhoid fever is caused by Salmonella typhi. The definitive diagnosis can be made by isolation of Salmonella typhi from blood, bone marrow or other body fluids. To support the clinical diagnosis of typhoid fever in Indonesia, where most hospitals and health centres haveno facilities for cultures, a rapid test for the detection of lipopolysaccharides (LPS) Salmonella typhi-specific IgM antibodies was evaluatedon serum samples from patients with typhoid fever. This study is proposed to know the rapid test diagnostic value for the detection oflipopolysaccharides (LPS) Salmonella typhi-specific IgM antibodies. A cross sectional, observational analytical study on 27 typhoidfever and 25 dengue hemorrhagic fever patients of the Dr. Soetomo Hospital, Dr. M Soewandhi General Hospital and Gotong-RoyongClinic has been conducted from January – May 2007. The diagnosis of typhoid fever patients was based on positive gall culture whilethe diagnosis of dengue hemorrhagic fever was based on negative gall culture, positive serology examination for dengue hemorrhagicfever and a recovery from dengue hemorrhagic fever with standard treatment. The sera from patients were examined using a rapid testfor the detection of lipopolysacharides (LPS) Salmonella typhi specific IgM antibodies from Amgenix Onsight of the first blood samples(collected on admission to the hospital) the rapid test for IgM antibodies showed the following: sensitivity 70.4%, specificity 80.0%,positive predictive value 79.2%, negative predictive value 71.4%, diagnostic efficiency 75% respectively. Of the second blood samples(collected 2–3 weeks during the illness) therapid test for IgM antibodies showed the following: sensitivity 88.9%, positive predictive value 82.8%, negative predictive value 87.0%, and diagnostic efficiency 84.6% respectively. The rapid test for IgM antibodies has a high diagnostic value for typhoid fever. The assay uses stabilized components which can be stored at room temperature; the test does notrequire special equipment and may be used in health centres that have no facilities for culture.